Application of interference fits on cylindrical monochromator crystals to overcome clamping and cooling deformations. (13th February 2019) - Stimson, Joshua; Ward, Michael; Sutter, John; Diaz-Moreno, Sofia; Alcock, Simon; Docker, Peter
Abstract : A novel monochromator assembly design utilizing an interference fit is suggested, tested and analysed and a comparison has been made with previous work performing similar tests on conventional side‐clamped crystal‐cooling designs. The new design was found to have an order of magnitude less deformation and a high level of repeatability without using indium foil. Abstract : In order to provide adequate cryogenic cooling of both existing and next‐generation crystal monochromators, a new approach to produce an optimum thermal interface between the first crystal and its copper heat exchanger is proposed. This will ensure that the increased heat load deposited by higher X‐ray powers can be properly dissipated. Utilizing a cylindrical silicon crystal, a tubular copper heat exchanger and by exploiting the differing thermal and mechanical properties of the two, a very good thermal interface was achieved at liquid‐nitrogen temperatures. The surface flatness of the diffracting plane at one end of the cylindrical crystal was measured at room temperature while unconstrained. The crystal was then placed into the copper heat exchanger, a slide fit at room temperature, and then cooled to liquid‐nitrogen temperature. At −200°C the slide fit became an interference fit. This room‐temperature `loose' fit was modelled using finite‐element analysis to obtain the desired fit at cryogenic temperatures by prescribing the fit at room temperature. Under these conditions, the diffraction surface was measured for distortion due to thermal and mechanical clamping forces. The total deformation was measured to be 30 nm, an order of magnitude improvement over deformation caused by cooling alone with the original side‐clamped design this concept method is set to replace. This new methodology also has the advantage that it is repeatable and does not require macro‐scale tools to acquire a nanometre‐accuracy mounting.